Traumatizing Oneself—Deep Wrist Injuries Self‐Inflicted with Suicidal Intention are Associated with More Severe PTSD Symptomatology than Similar Injuries from Accidents. Issue 4 (9th March 2020) - Westermair, Anna Lisa; Matzkeit, Nico; Waldmann, Annika; Stang, Felix; Mailänder, Peter; Schweiger, Ulrich; Kisch, Tobias
Abstract : Objective: As suicide attempts by definition entail at least some threat to physical integrity and life, they theoretically qualify as an A1 criterion for posttraumatic stress disorder (PTSD). This study uses the unique opportunity of deep wrist injuries to quantify the effect of intentionality on PTSD rates by comparing suicide attempt survivors with patients who sustained accidental injuries similar in mechanism, localization, and extent. Method: Patients who had been admitted with an acute deep wrist injury from 2008 to 2016 filled out the revised Impact of Event Scale and reported other known PTSD risk factors. Mental morbidity and intentionality of the injury were determined by psychiatric consultation during the index hospitalization. Results: Fifty‐one patients were followed up (72.5% male, 92.2% Caucasian, mean age at injury 42.3 ± 17.5 years, 72.5% accidental injuries), on average 4.2 ± 2.9 years after their injury. The intentionality of the injury alone predicted the severity of intrusions, avoidance, hyperarousal, and probable PTSD (aOR = 14.0). Conclusions: Traumatization in the context of a suicide attempt may be a hitherto unknown PTSD risk factor. Patients after suicide attempts, especially medically serious attempts, should be monitored for PTSD symptoms.